Comparison of DNA extraction methods to detect Salmonella spp. in tap water - Ocepek, Matjaž (Slovenian veterinary research, 2011)
Bacteria of the genus Salmonella cause a global health problem related to contaminated foodstuffs and faecally-polluted water supplies. The aim of our work was to determine the efficiency and rapidness of Salmonella detection in spiked tap water samples by comparison of different methods for DNA extraction. Water samples were spiked with different Salmonella loads. Four DNA extraction methods were employedČ foodproof Sample Preparation Kit I (Biotecon Diagnostics) and QIAamp DNA Stool Mini Kit (Qiagen) for DNA extraction after an overnight enrichment step, and Adiapure Water DNA Extraction and Purification Kit (Adiagene) and SmartHelix Complex Samples DNA Extraction Kit (developed recently in our laboratory) for direct DNA extraction. The extracted DNA was subjected to PCR amplification using Salmonella genus-specific primer pair. The SmartHelix extraction kit proved tobe more efficient than the Adiapure Water kit for direct detection of Salmonella DNA in water. The overnight enrichment step improved the detection of Salmonella spp. in samples spiked with low bacterial load, however it extended the analysis time. Results suggest that the newly developed SmartHelix extraction kit should be regarded as a considerable choice when rapid detection of pathogens in water samples is aimed for to prevent disease outbreaks and support safe food assurance.
Keywords: analysis; Food safety; Polymerase chain reaction; Salmonella; Water